2012
DOI: 10.1016/j.jaci.2012.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor–bearing exosome secretion from human mechanically stimulated bronchial epithelial cells in vitro and in vivo

Abstract: Background Tissue factor (TF), a primary initiator of blood coagulation, also plays a pivotal role in angiogenesis. TF expression in the airways is associated with asthma, a disease characterized in part by subepithelial angiogenesis. Objectives To determine potential sources of TF and the mechanisms of its availability in the lung microenvironment. Methods Normal Human Bronchial Epithelial (NHBE) cells grown in air-liquid interface (ALI) culture were subjected to a compressive stress of 30 cmH2O; this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 45 publications
(58 reference statements)
7
107
1
Order By: Relevance
“…We previously showed that compressive stress at 30 cm H 2 O increases TF mRNA expression in NHBE cells (21). Here, we examined if TF mRNA expression is dependent on the magnitude of pressure.…”
Section: Compressive Stress Increases Tf Mrna Expression In Nhbe Cellmentioning
confidence: 92%
See 3 more Smart Citations
“…We previously showed that compressive stress at 30 cm H 2 O increases TF mRNA expression in NHBE cells (21). Here, we examined if TF mRNA expression is dependent on the magnitude of pressure.…”
Section: Compressive Stress Increases Tf Mrna Expression In Nhbe Cellmentioning
confidence: 92%
“…We previously reported that TF expression is significantly higher in the airway epithelium and BAL fluid from subjects with asthma versus normal subjects (21). Here, we examined if the increase in TF expression in patients with asthma can be recapitulated in an allergic mouse model of asthma.…”
Section: Tf Is Elevated In the Bal Fluid Of Ova-challenged Micementioning
confidence: 94%
See 2 more Smart Citations
“…They may also contribute to the inflammation and remolding of the asthma airway (9,10). Mononuclear cells are the key cell type to express TF and are the primary source of blood-borne TF in vitro and in vivo (11).…”
Section: Introductionmentioning
confidence: 99%